STUDI SIFAT FISIK DAN MEKANIK PARENKHIM PELEPAH DAUN KELAPA SAWIT UNTUK PEMANFAATAN SEBAGAI BAHAN ANYAMAN - Yazid Ismi Intara; Banun Dyah P (AGROINTEK, 2012)
This study explored the use of parenchyme of palm (Elaeis guinensis Jack) leave sheat as material for woven craft. Important elements of parenchyme including cellulose, hemicellulose, lignin, minerals and extracted components, determine its strength. Mechanical properties studied in this work were density, elastic modulus, tensile strength, yield strength, tensile stress, deformation, and elasticity-plasticity. Results showed that in certain size, palm leave sheat parenchyme can be used to replace bamboo or rattan in woven craft. However, size of sheat was much larger than that of bamboo or rattan, whilst the fiber was also too rough. It was also difficult to extract the parenchyme